2021
DOI: 10.1108/mf-09-2020-0471
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CEO political ideology on labor relations and firm value

Abstract: PurposeThis article aims to examine the influence of chief executive officer (CEO) internal political beliefs on labor relations. Prior research has paid little attention to channels through which the internal personal value system of managers enhances or deteriorates firm value. The authors provide evidence consistent with CEOs adopting labor policies impacting incumbent management–labor relationships based upon their political ideologies.Design/methodology/approachThe research design tests the impact of CEO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Because it is difficult to accurately quantify executive tendencies, UET focuses on demographics and Upper echelons in college sport experiences to proxy lead executive decision-making (e.g. Carpenter et al, 2004;Kim et al, 2021). The UET framework is commonly used in a wide range of academic disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because it is difficult to accurately quantify executive tendencies, UET focuses on demographics and Upper echelons in college sport experiences to proxy lead executive decision-making (e.g. Carpenter et al, 2004;Kim et al, 2021). The UET framework is commonly used in a wide range of academic disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Managers who hold political beliefs are able to integrate their own political perceptions and behavioral preferences into strategic choices, shaping organizational behaviour and decision outcomes [34]. Some scholars have studied for the U.S. scenario and found that managers' political beliefs not only promote corporate social responsibility [35], but also narrow the pay gap between management teams [36], improve labor relations [37], and enhance corporate value [38]. Studying corporate behavior from executives' political ideology is becoming a hot research topic in recent years [39].…”
Section: Introductionmentioning
confidence: 99%